2013
DOI: 10.1371/journal.pone.0056522
|View full text |Cite
|
Sign up to set email alerts
|

Significant Molecular and Systemic Adaptations after Repeated Sprint Training in Hypoxia

Abstract: While intermittent hypoxic training (IHT) has been reported to evoke cellular responses via hypoxia inducible factors (HIFs) but without substantial performance benefits in endurance athletes, we hypothesized that repeated sprint training in hypoxia could enhance repeated sprint ability (RSA) performed in normoxia via improved glycolysis and O2 utilization. 40 trained subjects completed 8 cycling repeated sprint sessions in hypoxia (RSH, 3000 m) or normoxia (RSN, 485 m). Before (Pre-) and after (Post-) trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
328
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(378 citation statements)
references
References 50 publications
29
328
1
4
Order By: Relevance
“…Our main finding is that 12 RSH training sessions, compared with RSN, did not improve RS performance, when determined in 12 separate test sessions with and without prior exhausting exercise at sea level and normobaric hypoxia (FiO2=13. 3,4 . Such divergence could be explained by the absence of or controversial application of criteria for exhaustion/task failure 3,4 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our main finding is that 12 RSH training sessions, compared with RSN, did not improve RS performance, when determined in 12 separate test sessions with and without prior exhausting exercise at sea level and normobaric hypoxia (FiO2=13. 3,4 . Such divergence could be explained by the absence of or controversial application of criteria for exhaustion/task failure 3,4 .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the proposed effect of RSH on RS performance was observed without prior exercise and in normoxic conditions [2][3][4][5] . Whether such effect can be extrapolated to situations including prior exhaustive exercise (such as at the end of a XC-ski or bicycle race) and hypoxic conditions remains uncertain; if confirmed, RSH could be of major relevance for athletic competitions critically determined in fatiguing conditions and/or carried out at altitude 7 .…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Following four weeks of cycle sprint training (3 sets of 5×10 sec all-out repeated sprints with 5 min recovery), Faiss et al [263] showed that moderately trained males had improved activity of lactate dehydrogenase, suggesting an increased capacity for pH regulation [264]. Therefore in the present study, the second and third sets of repeated sprints would have been performed with a considerable stress on the mechanisms involved in intracellular pH regulation [227].…”
Section: Rsa -Training and β-Alanine Supplementationmentioning
confidence: 83%